Implementation of Functions Legislation Council of Representatives of the Regional Provincial North Sulawesi Year 2016-2018 - Likuajang, Rafli; Pangkey, Itje; Tumbel, Goinpeace (Technium Social Sciences Journal, 2021)
Based on field data in 2016-2018, 18 regional regulations have been successfully enacted. However, according to information from the legal bureau, all regional regulations from 2016-2018 have been sourced from regional executive regulations, and there are no DPRD-initiated regulations. Every year, draft regional regulations on DPRD initiatives are included in the priority scales of the regional regulations but have not been enacted. Quality of DPRD members. With the limited quality of board members in understanding legal drafting for the formation of regional regulations, the board members encourage establishing a technical guidance program related to legal drafting. However, in its implementation, it is the members of the council who do not take it seriously, so the substance of the materials for technical guidance is not implemented in forming regional regulations. This study aims to analyze how the implementation of the legislative function of the DPRD of North Sulawesi Province for the 2016-2018 period. In connection with one of the council's functions in terms of legislation, namely forming regional regulations. In it further analyzes the things that make the DPRD less than optimal in the field of legislation. So that it gets a result from the discussion that can be a reference for improving the system and scientific literacy material in the study of public administration management. The approach used in this research is qualitative—data collection using interviews, observations and documentaries. Data analysis uses data analysis techniques according to the Miles and Huberman model, namely Data Reduction, Data Display, and Verification. The results showed that implementing the legislative function of the DPRD of North Sulawesi Province has not run optimally. This refers to the achievements of local initiative regulations, all of which are sourced from regional executive regulations. The timeliness of DPRD in formulating regional regulations has not been optimal. The process of forming regional regulations is less than optimal, hampered by several factors, including the Absence of DPRD members at the special committee meeting for regional regulations, the quality of DPRD members, more lengthy procedures for DPRD initiatives.